2005
DOI: 10.1073/pnas.0500398102
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic differences arise during the lifetime of monozygotic twins

Abstract: Monozygous twins share a common genotype. However, most monozygotic twin pairs are not identical; several types of phenotypic discordance may be observed, such as differences in susceptibilities to disease and a wide range of anthropomorphic features. There are several possible explanations for these observations, but one is the existence of epigenetic differences. To address this issue, we examined the global and locus-specific differences in DNA methylation and histone acetylation of a large cohort of monozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
2,132
12
55

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,202 publications
(2,252 citation statements)
references
References 16 publications
53
2,132
12
55
Order By: Relevance
“…Microarray studies confirmed a decrease in DNA methylation with age, while site‐specific analysis indicated an increase in variability of DNA methylation with age. The latter was first noted in monozygotic twins, and subsequently in unrelated individuals (Fraga et al ., 2005; Martin, 2005; Poulsen et al ., 2007; Kaminsky et al ., 2009; Martino et al ., 2011). These studies also supported the idea that DNA methylation showed reduced stringency in maintenance over the lifespan, resulting in an increase in interindividual variability along with the overall decrease in DNA methylation.…”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray studies confirmed a decrease in DNA methylation with age, while site‐specific analysis indicated an increase in variability of DNA methylation with age. The latter was first noted in monozygotic twins, and subsequently in unrelated individuals (Fraga et al ., 2005; Martin, 2005; Poulsen et al ., 2007; Kaminsky et al ., 2009; Martino et al ., 2011). These studies also supported the idea that DNA methylation showed reduced stringency in maintenance over the lifespan, resulting in an increase in interindividual variability along with the overall decrease in DNA methylation.…”
Section: Dna Methylation Dynamics During Agingmentioning
confidence: 99%
“…Epigenetic drift is now understood to comprise age‐related changes in the epigenome that include those that are acquired environmentally as well as stochastically (Fraga et al ., 2005; Fraga & Esteller, 2007; Kaminsky et al ., 2009; Hannum et al ., 2013; Teschendorff et al ., 2013). Early indications of epigenetic drift were noted in cell culture studies, after the observation that clones of a single cell line became epigenetically divergent upon multiple passages (Humpherys et al ., 2001).…”
Section: Epigenetic Drift Vs the Epigenetic Clock: Two Phenomena Undmentioning
confidence: 99%
“…However, studying age-varying methylation sites captures divergence of methylomes between individuals over time, usually described as epigenetic drift . Studies on epigenetic drift have been conducted using various methods, which include observing methylation differences between monozygotic twins [6,7], counting extreme methylation outliers as epigenetic mutations [8] and computing methylation variability using a test of heteroskedasticity [1,9].
10.1080/15592294.2018.1521222-F0001Figure 1.Simplified plots illustrating the concept of age-associated and age-varying methylation patterns.
…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that these factors may strengthen DNA methylation stability or influence its deviation between genetically identical individuals over time (Shah et al ., 2014). Studies of monozygotic twins demonstrate widening epigenetic divergence over time, which correlates to greater interindividual variability in phenotype (Fraga et al ., 2005). Fraga et al .…”
Section: Introductionmentioning
confidence: 99%
“…Fraga et al . (2005) showed growing DNA methylation differences with age, especially in twin pairs whose lifestyle, location, and/or health status were disparate (Fraga et al ., 2005), defining DNA methylation as a dynamic mark able to record a variety of exposures at the cellular level. Recent studies have also demonstrated that methylation across tissues and cell types can be correlated with chronological age, indicating that DNA methylation certainly works as a function of age or can be accelerated by different conditions, most notably in the setting of cancer (Hannum et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%